(untitled) (Al-Mansour Journal, 2025)
The Two words that inform the title of this paper, namely ‘treason’ and ‘compassion’ are quite suggestive in the elegant sense that they actually define the stunning realities in Flaubert’s novel. They impinge on our minds the negative as well as the positive realities and magnificently isolate for us a writer who is in full control of his creation. Emma starts by marrying a man who disastrously fails to satisfy her and soon she feels wretched. As a way out of her miserable state, she first befriends Randolph as a lover. Then she leaves him and befriends Léon only to go back to Randolph to help her financially. But he let her down. She, then, feels so wretched that she ends her life by poisoning herself. A grief-stricken Charles, Emma’s husband, has been unaware of Emma’s financial troubles and her miserable state. He remains devoted to his deceased wife as he struggles to pay her debts. After discovering love letters from Randolph and Léon, Emma’s lovers, he becomes increasingly sad, blaming Emma’s sad end on fate. Shortly afterwards he dies. Then left alone, Berthe, his daughter, ends by working at a cotton factory. The message of Flaubert’s novel is quite enlightening: “In writing Madam Bovary, Flaubert criticises the values of the bourgeois class through events leading to Emma’s downfall.” (1)